Biomass Growth and Composition of Azolla (Azolla Pinnata R. BR.) Supplemented With Inorganic Phosphorus in Outdoor Culture (SAARC Journal of Agriculture, 2021)
An experiment was conducted to know the effect of supplemental phosphorus on biomass growth and composition of a floating aquatic fern, Azolla pinnata, cultured in a pit system for 21 days with 4 levels of phosphorus (0, 5, 10, and 15 ppm) supplementation. Water quality parameters of the pits were within a suitable range for A. pinnata culture. It was observed that fresh and dry weights of A. pinnata increased with phosphorus supplementation up to 10 ppm. Doubling time was the fastest when the culture medium was supplemented with 10 ppm of phosphorus. Phosphorus content of A. pinnata was proportional to the phosphorus supplementation in the culture medium. Supplementation of phosphorus also improved the protein and lipid contents of A. pinnata. It was concluded that supplementation of 10 ppm phosphorus to water used for culturing A. pinnata is optimum under outdoor conditions.SAARC J. Agric., 19(1): 177-184 (2021)